Analisis Pengaruh Sektor Perdagangan dan sektor Pertanian terhadap Pertumbuhan Ekonomi - Rika Rahmadina Putri,S.E.I., M.Si; Mudzakir Ilyas; Evi Rukmana (Sekolah Tinggi Ekonomi Islam Al-Furqon Prabumulih, 2023)
This research aims to determine the Influence of the Trade Sector and the Agriculture Sector on the Economic Growth. This study is a quantitative research using multiple linear regression analysis method, the trade sector (X1) with a t-value of -3.264 is greater than the t-table value of -1.812, indicating that (-3.264 > -1.812) (the t-table value is changed to negative because the t-value is negative), and the significance value is 0.009. It is therefore stated that the trade sector (X1) has a negative influence on the economic growth of Prabumulih City (Y) on a partial basis. The agriculture sector (X2) with a t-value of 18.268 is greater than the t-table value of 1.812 (18.268 > 1.812), and the significance value is 0.000. It is thus stated that the agriculture sector (X2) has a positive and significant influence on the economic growth of Prabumulih City (Y) on a partial basis.Based on the results of the simultaneous or F-test, it shows that the trade sector and the agriculture sector with an F-value of 385.364 is greater than the F-table value of 4.103 (385.364 > 4.103), and the significance value is 0.000. It is therefore declared that collectively, the Trade Sector (X1) and the Agriculture Sector (X2) have a positive and significant influence on the economic growth of Prabumulih City (Y).